A decision support tool for potato late blight management: Assessing its usability for women farmers to achieve equitable impacts in the highlands of Peru - Pérez, W.; Kawarazuka, Nozomi; Fonseca, C.; Andrade-Piedra, J.L. (Informa UK Limited, 2024)
Decision support tools in agriculture help farmers make science-informed decisions rather than experience-dependent ones, which is increasingly important in the context of climate change. However, these tools often fail to accommodate diverse users in terms of their contents, ease of use, and dissemination strategies. The objectives of this study are 1) to understand gender roles in potato production, 2) to understand men and women’s knowledge and perceptions of pesticide application, and 3) assess the usability of a handheld decision support tool for potato late blight control from the perspective of gender in Peru. A qualitative participatory assessment was carried out in two communities in the Andes to explore not only the technical usability of the tool for men and women farmers, but also gender roles, knowledge, and perceptions of pest and disease management that determine household decisions on pesticide use. The findings confirmed that women farmers face challenges to using the tool, based on both technical and sociocultural aspects. Furthermore, women farmers play a significant role in potato production in general, and their involvement in late blight management is likely to contribute to making appropriate household decisions on the use of pesticides, thereby mitigating overall health and environmental risks. The study concludes with recommendations for modifying the tool for women users as well as incorporating women’s perspectives at the design stage.